Acclimatization to Hearing Aids by Older Adults. Issue 1 (January 2021) - Wright, Dominique; Gagné, Jean-Pierre
Abstract : Objectives: Audiologists and hearing aid users (HAUs) generally agree that an adaptation period is needed following the first hearing aid (HA) experience. The main purpose of this study is to investigate the acclimatization of older adult listeners with hearing loss to HAs using listening effort and behavioral measures. Design: Participants (N=47) were older adults with mild to moderately severe sensorineural hearing loss. Thirty-two participants were new HAUs and 15 participants were experienced HAUs. New HAUs were randomly assigned to one of two groups: noise reduction algorithms and directional microphones activated or noise reduction algorithms and directional microphones deactivated. Speech recognition in noise and listening effort were assessed on 8 different occasions during a 10-month period. A dual-task paradigm was used to measure the listening effort deployed to recognize speech in noise. The primary task consisted of the Hearing in Noise Test which also served as the behavioral speech in noise measure. The secondary task was a tactile pattern-recognition task in which participants had to identify a sequence of three tactile stimuli that varied in duration. The two listening effort outcomes were the proportional dual-task cost and the response time on the secondary task. Cognitive abilities, including working memory and speed of processing, were evaluated using the Reading Span Test and the Digit Symbol Substitution Test, respectively. Results: Results show a significant time*group interaction. Both groups of new HAUs showed improvement over time in speech in noise performances (change of ~2 dB signal to noise ratio) and the experienced HAUs did not improve over time. The acclimatization effect was observed over a period of 4 weeks. There was no significant change over time on both measures of listening effort. There was no association between amplitude of acclimatization and the cognitive abilities measured. Conclusion: An acclimatization effect following HA experience was observed. Specifically, the new HAUs displayed a clinically significant change of 2 dB in signal to noise ratio on the Hearing in Noise Test 4 weeks following their initial fitting. The acclimatization effect is not correlated to cognitive abilities.